Environmental, social, and governance (ESG) disclosure and firm performance: a case study of Malaysian plantation listed companies / Nik Nur Azmina Azhar - Azhar, Nik Nur Azmina (2024)
Nowadays, Bursa Malaysia is actively seeking registered companies in Malaysia to report their Environmental, Social, and Governance (ESG) information for public especially after Bursa Malaysia has introduced the Simplified ESG disclosure guideline to help the Small, and Medium Enterprise (SME) in disclosing the ESG information. With this introduction, it makes the listed companies triggered to disclose their ESG information. Institutional theory states that when there is pressure on the companies, they will follow the stipulated Bursa Requirements by disclosing the ESG information in more details especially plantation companies since this sector is more exposed to the ESG issues as compared to the other sectors. The objective of this research is to examine the relationship between ESG disclosure and firm performance of plantation listed companies in Malaysia for each individual ESG pillars. This research uses stratified sampling in choosing the sample which are main listed companies on Bursa Malaysia and Shariah compliance. In total, 32 plantation companies meet the requirement of the sample and ESG data are collected from the annual report. Every company is observed for five years from 2018 to 2022. This research uses 30 indicators in measuring the disclosure of information for Environmental Disclosure (ED), Social Disclosure (SD), and Governance Disclosure (GD). In measuring the firm performance, this research uses Return on Equity (ROE), Earnings Before Interest and Taxation (EBIT), and Tobin’s Q (TQ). The results show that ED has significant relationship with ROE and TQ, but insignificant relationships with EBIT. SD has significant relationship with ROE and EBIT, but insignificant relationships with TQ. All proxies used have insignificant relationship with GD. The findings of this research help to uncover how plantation companies respond to sustainability-related institutional pressures, offering insights into the alignment between corporate practices and societal expectations.